COMBINATION TREATMENTS USING VANCOMYCIN WITH IMMUNOMODULATORS TO MODULATE STAPHYLOCOCCAL ARTHRITIS - Dutta, Sulagna; Bishayi, Biswadev (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Staphylococcus aureus is an intensely studied organism to cause septic arthritis. This study aims at using vancomycin to mitigate the bacterial burden in mice infected with pathogenic strain of S. aureus which is combined with the in vivo inhibition of nitric oxide (NO) and prostaglandin (PG) levels via aminoguanidine (AMG) and meclofenamic acid (MFA), respectively, to modulate the inflammatory conditions in bacterial arthritis. Methods: Synergy between the drugs was performed via Chequerboard. The clinical signs of septic arthritis were recorded on the 3 days post-infection (DPI) including induction of arthritis, measuring bacterial density in blood, spleen and synovial tissue, blood parameters and cytokines (tumor necrosis factor alpha (TNF Î±), interferon gamma (IFN Î³), interleukin-6 [IL-6], IL-10) levels, myeloperoxidase (MPO) and lysozyme activities, and histopathological examinations of the synovial joints. Results: S. aureus infection showed a significant increase in bacterial densities and inflammation. AMG/MFA treatment alone showed no bacterial clearance since endogenous NO or PG had been limited for bacterial killing but observably down-regulated inflammatory upshots. Vancomycin cotreatment with AMG or MFA showed maximum mitigation of bacterial load as well as the inflammatory conditions, articular repair and decreased in the percentage of induction of arthritis. Conclusion: Diminution of S. aureus burden in tissues via vancomycin and suppression of inflammatory by AMG or MFA may have shown a visibly potent therapeutic remedy to combat septic arthritis. Keywords: Aminoguanidine, Meclofenamic acid, Septic arthritis, Staphylococcus aureus, Vancomycin rd , 9 th , and 15 th